The application of procyanidins in diabetes and its complications: a review of preclinical studies - Zhang, Yongchuang; Li, Mengna; Liu, Haoyuan; Fan, Yongfu; Liu, Huan Huan (Frontiers in Pharmacology, 2025)
Diabetes mellitus (DM) and its various complications, including diabetic nephropathy, retinopathy, neuropathy, cardiovascular disease, and ulcers, pose significant challenges to global health. This review investigates the potential of procyanidins (PCs), a natural polyphenolic compound, in preventing and managing diabetes and its complications. PCs, recognized for their strong antioxidant, anti-inflammatory, and anti-hyperglycemic properties, play a crucial role in reducing oxidative stress and enhancing endothelial function, which are essential for managing diabetic complications. This review elucidates the molecular mechanisms by which PCs improve insulin sensitivity and endothelial health, thereby providing protection against the various complications of diabetes. The comprehensive analysis underscores the promising therapeutic role of PCs in diabetes care, indicating the need for further clinical studies to confirm and leverage their potential in comprehensive diabetes management strategies.